Interpersonal Communication and Customer Loyalty: A Case Study at a Travel Agency - Fiqih Hidayah Tunggal Wiranti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research takes the title of interpersonal communication and customer loyalty. This research is to find out how interpersonal communication has an impact on customer loyalty. The approach taken is a descriptive qualitative approach by analyzing the travel agency and customers both through observation and unstructured interviews. The results obtained from the research conducted indicate that interpersonal communication carried out by travel agents shows openness in receiving suggestions, empathy for the wishes of customers, reciprocal support, positive feelings by providing comfort and equality without distinguishing between customers. With the interpersonal communication strategy carried out by travel bureau x with customers it provides a sense of satisfaction with the services provided, emotional bonds, trust, convenience and a pleasant experience. This has led to the emergence of customer loyalty, this is evidenced by the communication related to planning a return trip by the customer with the travel agency x. The importance of interpersonal communication with customers helps the travel agency in meeting customer wants and needs. This has led to the emergence of customer loyalty, this is evidenced by the communication related to planning a return trip by the customer with the travel agency x. The importance of interpersonal communication with customers helps the travel agency in meeting customer wants and needs. This has led to the emergence of customer loyalty, this is evidenced by the communication related to planning a return trip by the customer with the travel agency x.